KEBERADAAN DAN KELIMPAHAN FITOPLANKTON SEBAGAI SALAH SATU INDIKATOR KESUBURAN LINGKUNGAN PERAIRAN DI WADUK RIAM KANAN - Dini Sofarini (Universitas Lambung Mangkurat, 2012)
Evaluated from fitoplankton abundance index, has known that the condition of territorial Riam Kanan Basin water can be classified as a good condition or pertained at light contamination, where fitoplankton as first producer represent the especial link in giration the underwater food chain. Hence, obtainable territorial waters fertility with the make-up of amount of fitoplankton or the fitoplankton abundance index in territorial water represent one of indicator of territorial waters fertility.